The Disavowal of Difference: Accessing Class and Symbolic Boundary-Drawing in Interviews - Faber, Stine Thidemann (Qualitative Studies, 2012)
In this article I recount and reflect on methodological issues raised in my research about class representations and symbolic boundary drawing. The article discusses different aspects of accessing class by way of interviews (thereby privileging ‘talk’ as a source of data), the dilemmas involved in conducting the interviews (including the need for paying attention to classed power inherent in the research setting), and the challenges and associated problems of representing the experience of others, especially when researching across difference.